Optimizing Kindergarten School Leadership Development through Multi-Level Mentoring: A Cascading Network Approach - Dangu Asmoro, Sudrajat (JGSD: Jurnal Guru Sekolah Dasar, 2024)
This study investigates the impact of Multi-Level Marketing (MLM) mentoring methodology on transformational leadership development among kindergarten teachers in Grobogan Regency. Employing a mixed-methods approach, the research examines how hierarchical mentorship strategies influence professional identity and organizational commitment. Quantitative and qualitative findings reveal significant improvements in leadership competencies, with key mediating factors including organizational identification and leader-member exchange dynamics. The research addresses systemic challenges in educational leadership coaching, demonstrating the potential of innovative mentoring frameworks to enhance teachers' professional growth and effectiveness in early childhood education settings.